2017
DOI: 10.1002/hyp.11112
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying annual groundwater recharge and storage in the central Sierra Nevada using naturally occurring35S

Abstract: Identifying aquifer vulnerability to climate change is of vital importance in the Sierra Nevada and other snow-dominated basins where groundwater systems are essential to water supply and ecosystem health. Quantifying the component of new (current year's) snowmelt in groundwater and surface water is useful in evaluating aquifer vulnerability because significant annual recharge may indicate that streamflow will respond rapidly to annual variability in precipitation, followed by more gradual decreases in recharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Few prior applications of sodium‐22 have been published (Kaste et al, ) and are mostly limited to lake residence time studies (Sakaguchi et al, ). Applications of sulfur‐35 are more widespread, and recent studies have demonstrated its use to derive the residence time of managed aquifer recharge (Clark et al, ; Urióstegui et al, , ) and alpine catchments (Urióstegui et al, ) in conjunction with other age tracers. Tritium and oxygen‐18 combined are powerful tracers for watersheds with similar characteristics, while sodium‐22 and sulfur‐35 would be more beneficial if shorter flow paths dominate the stream flow generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few prior applications of sodium‐22 have been published (Kaste et al, ) and are mostly limited to lake residence time studies (Sakaguchi et al, ). Applications of sulfur‐35 are more widespread, and recent studies have demonstrated its use to derive the residence time of managed aquifer recharge (Clark et al, ; Urióstegui et al, , ) and alpine catchments (Urióstegui et al, ) in conjunction with other age tracers. Tritium and oxygen‐18 combined are powerful tracers for watersheds with similar characteristics, while sodium‐22 and sulfur‐35 would be more beneficial if shorter flow paths dominate the stream flow generation.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfur‐35 immobilization (e.g., uptake by vegetation or soil microbial processes) has been discussed in prior studies (Böhlke & Michel, ; Michel et al, ) and needs to be investigated further. Analysis of the stable sulfur isotopic composition (sulfur‐34/sulfur‐32) of sulfate in hydrological compartments is promising (Urióstegui et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the annual pulse of meltwater percolates toward the saturated zone (Hammond, Harpold, Weiss, & Kampf, 2019). In the Sierra Nevada of California, analysis of shortlived cosmogenic sulfur isotopes revealed that less than 15% of freshet streamflow originated from the previous winter's snow pack and that a significant fraction of the annual snowmelt was recharging the groundwater system (Urióstegui et al, 2017). Snowmelt is a more efficient contributor to streamflow (through shallow runoff) than rainfall because the concentrated period of infiltration allows less time for evapotranspiration compared to intermittent precipitation and snowmelt generally occurs in the spring when potential evapotranspiration is lower.…”
Section: Recharge From Rain and Snowmeltmentioning
confidence: 99%
“…Baraer et al (2015) found that groundwater contributes 24–80% of dry season stream discharge in four proglacial valleys of the Cordillera Blanca in the northern Peruvian Andes, while Wang et al (2017) found that groundwater contributed 38% of streamflow in a glacierized watershed of the Tianshan Mountains in China. More recent work has increased the spatial and temporal resolution of results, examined fine‐scale groundwater flow paths and made use of new tracers such as chloride isotopes (Shaw et al, 2014), sulfur isotopes (Urióstegui, Bibby, Esser, & Clark, 2017), and dissolved noble gasses (Gleeson et al, 2018).…”
Section: Quantifying Groundwater Contribution To High Mountain Riversmentioning
confidence: 99%
See 1 more Smart Citation